Biochemistry and Molecular Biology, 6th edition. Edited by Despo Papachristodoulou, Alison Snape, William H. Elliott and Daphne C. Elliott. Oxford University Press, 2018. Pp. 640. Price GBP 39.99, paperback, ISBN 9780198768111. Issue 11 (2nd November 2018) - Jacquot, Jean-Pierre
Abstract : The sixth edition of Biochemistry and Molecular Biology by edited by Despo Papachristodoulou, Alison Snape, William H. Elliott and Daphne C. Elliott is reviewed. Abstract : The sixth edition of Biochemistry and Molecular Biology by edited by Despo Papachristodoulou, Alison Snape, William H. Elliott and Daphne C. Elliott is reviewed.